Domiciliation Trend of Panstrongylus rufotuberculatus in Colombia (2002)
ABSTRACT: The present paper presents evidence of the domiciliation of Panstrongylus rufotuberculatus in La Gardenia, Colombia through the collection of 2 unhatched eggs, 81 nymphs and 10 adults (4 males and 6 females), from 2 rural houses. The transmission risk indicators of Trypanosoma cruzi by P. rufotuberculatus in La Gardenia, were: domiciliary infestation 7.5%, density 2.35, colonization 66.6%, overcrowding 31.33, natural infection 4.6%, and relative infection 2.5%. These results and findings in Peru and Argentina, show that P. rufotuberculatus has a potential success in domiciliation and could some day become an alternate vector of American trypanosomiasis.